The African adventure of Conrad, Céline and Gide. Journey to the Land of Darkness - (:unkn) unknown (My University, 2017)
At the beginning of the 20th century, equatorial Africa attracted more and more adventurers in search of a change of scenery or easy wealth. The notebooks and travelogues of several authors, who came into contact with the colonial world, give an unflattering representation of it in contrast with the deceptive official utopia. Behind the idea of progress dear to the colonialist discourse, immense pain and exactions of all kinds are revealed. Joseph Conrad in Au cœur des ténèbres (1899), Ferdinand Céline in Voyage au bout de la nuit (1932), and André Gide in his Voyage au Congo (1927), note the cruelty of the colonial model and denounce the dishonest and corrupt commercial practices of the European trading companies that plunder and destroy their concessions. Behind the sham of civilization lies a purely lucrative enterprise. In these works, the journey takes on the appearance of an initiatory ordeal, a descent into the underworld that leads to the heart of a still little explored equatorial Africa, but also to the heart of the darkness of an inhuman and brutal colonial system.
Keywords: African Research